PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN INFORMASI TAHUNAN PERUSAHAAN SERTA IMPLIKASINYA TERHADAP VOLUME PERDAGANGAN SAHAM PERUSAHAAN - Indra Lila Kusuma (Jurnal Akuntansi dan Pajak, 2015)
The objective of this research is to investigate whether there are significant influences between firm characteristic on annually disclosure level and its implication on trading volume activity, both directly and indirectly. Variables that used in this research were firm characteristic which its contents of industry type, firm size and firm age. Annually disclosure level of firm proxied by Disclosure index, and trading volume activity of firm proxied by total trading stock divide listed stock.This research used several companies as samples which listed in Indonesian Stock Exchange and classified in index LQ45 for the period of 2013. By using purposive sampling, there were 16 companies that used as samples. This research used analytical descriptive on secondary data.The results indicate that industry type firm size and age of the firm had no significant influence on annually disclosure level, annually disclosure level had no significant influence on trading volume activity. This result also shows that industry type, firm size and firm age had no significant influence with trading volume activity of firm, directly. And indirectly, firm characteristic through annually disclosure level of firm had no significant influence on trading volume activity of firm.